Microprocessor OCM-003 device for ozone concentration measuring - Gubarev, S.P.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I.; Nezovibat’ko, Y.N. (Вопросы атомной науки и техники, 2016)
In the paper, the OCM-003 type meter of ozone concentration operated in a gaseous environment with microprocessor control unit has been developed. Such device belongs to spectroscopic type meters. The measuring principle is based on the absorption of ultraviolet (UV) light at a wavelength of 254 nm. It was shown that the measurable ozone concentration range comprised 0.1…100 mg/l. The ozone meter is controlled by the PIC18F25K80 microprocessor-based controller produced by Microchip Technology Inc. The original software was developed. The possibility to developing a simple low-cost meter of ozone has been shown.